2013
DOI: 10.1073/pnas.1222295110
|View full text |Cite
|
Sign up to set email alerts
|

ATP-gated ion channels mediate adaptation to elevated sound levels

Abstract: The sense of hearing is remarkable for its auditory dynamic range, which spans more than 10 12 in acoustic intensity. The mechanisms that enable the cochlea to transduce high sound levels without damage are of key interest, particularly with regard to the broad impact of industrial, military, and recreational auditory overstimulation on hearing disability. We show that ATP-gated ion channels assembled from P2X 2 receptor subunits in the cochlea are necessary for the development of temporary threshold shift (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
129
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 40 publications
(53 reference statements)
5
129
0
Order By: Relevance
“…Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15]. After several decades of extensive work, the scientific community came to the realization that ATP is widely employed as a signaling molecule in multiple biological processes in both normal and pathophysiological conditions [9,11,[16][17][18][19][20][21][22][23][24]. The rapid progress in understanding and deciphering multiple molecular mechanisms of signaling revealed that ATP is a potent mediator of multiple signaling cascades, which may act through binding to, and nonhydrolytic activation of, P2X ionotropic receptors or G Electronic supplementary material The online version of this article (doi:10.1007/s11302-016-9520-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15]. After several decades of extensive work, the scientific community came to the realization that ATP is widely employed as a signaling molecule in multiple biological processes in both normal and pathophysiological conditions [9,11,[16][17][18][19][20][21][22][23][24]. The rapid progress in understanding and deciphering multiple molecular mechanisms of signaling revealed that ATP is a potent mediator of multiple signaling cascades, which may act through binding to, and nonhydrolytic activation of, P2X ionotropic receptors or G Electronic supplementary material The online version of this article (doi:10.1007/s11302-016-9520-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple past studies focused on understanding the implications of ATP-controlled signaling with respect to endogenous transmembrane transporters such as ion channels [17,19,20,24,[28][29][30][31], there is a recent interest in understanding how ATP controls the lytic action of pore-forming toxins (PFTs) [22,26,27,[32][33][34]. PFTs introduce unregulated conducting pathways into the host cell plasmalemma [35][36][37][38][39], which is expected to yield direct cytolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell patch clamp analysis showed that the sustained inward currents elicited by ATP application was absent from P2rX2 −/− inner and outer hair cells as well as RM epithelial cells, indicating that this conductance arose from a homomeric P2X 2 trimeric subunit configuration of the ATP-gated ion channels. Extending from this, the P2rX2 null mouse also lacked the extracellular fall in endocochlear potential and associated decrease in cochlear partition resistance that is evident when picolitres of ATP is injected into the endolymphatic compartment [7]. This finding suggests that all of the ATP-activated membrane conductance in cell lining that cochlear compartment is attributable to P2X 2 -type channels.…”
Section: Introductionmentioning
confidence: 77%
“…In the cochlea, ATP influences sound transduction, the endocochlear potential and neurotransmission, and underlies an intrinsic purinergic P2X 2 receptor-based humoral hearing adaptation mechanism that reduces hearing sensitivity as sustained sound levels increase [7]. However, native ATPinduced responses in many cochlear cells have not correlated well with known recombinant P2X receptor combinations [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation